Searching \ for '[OT:] Light bulb make square to sine wave' in subject line. ()
Make payments with PayPal - it's fast, free and secure! Help us get a faster server
FAQ page: www.piclist.com/techref/method/math.htm?key=sine
Search entire site for: 'Light bulb make square to sine wave'.

Exact match. Not showing close matches.
PICList Thread
'[OT:] Light bulb make square to sine wave'
2004\06\13@094749 by Jinx

face picon face
In response to

> X = 0.99999999 (repeating ad inifinitum)
>
> 10x = 9.999999999999 repeating
>
> 10x - x = 9x = 9.9999999 - .999999 = 9
>
> 9x = 9
>
> X = 1

I was sent

If a = b, then:

a^2 = a*b

a^2 - b^2 = (a*b) - b^2
(a-b)(a+b) = b(a - b)

(a+b) = b

Substitute the original a = b into the equation:

2b = b
2 = 1

--
http://www.piclist.com#nomail Going offline? Don't AutoReply us!
email spam_OUTlistservTakeThisOuTspammitvma.mit.edu with SET PICList DIGEST in the body

2004\06\13@111709 by Wouter van Ooijen

face picon face
> (a-b)(a+b) = b(a - b)

If a == b the (a-b) terms in the above line are a mathematical black
hole.

Wouter van Ooijen

-- -------------------------------------------
Van Ooijen Technische Informatica: http://www.voti.nl
consultancy, development, PICmicro products

--
http://www.piclist.com#nomail Going offline? Don't AutoReply us!
email .....listservKILLspamspam@spam@mitvma.mit.edu with SET PICList DIGEST in the body

2004\06\13@142745 by res0qrqr

picon face
> > (a-b)(a+b) = b(a - b)
>
> If a == b the (a-b) terms in the above line are a mathematical black
> hole.
>
> Wouter van Ooijen

No, they are perfectly well-defined and obey all the laws
of mathematics... until you get to the very last line:

2b = b    (everything's fine here)
therefore (NOT!)
2 = 1     (division by you-know-what error!)

Brian Aase

--
http://www.piclist.com#nomail Going offline? Don't AutoReply us!
email listservspamKILLspammitvma.mit.edu with SET PICList DIGEST in the body

2004\06\13@142749 by Russell McMahon

face
flavicon
face
> I was sent
>
> If a = b, then:
>
> a^2 = a*b
>
> a^2 - b^2 = (a*b) - b^2
> (a-b)(a+b) = b(a - b)
>
> (a+b) = b
>
> Substitute the original a = b into the equation:
>
> 2b = b
> 2 = 1

Took a few moments of staring :-)
(a-b)(a+b)=b(a-b)
BUT a=b so
(0)(2a) = b (0)
So either 0 = 0 (correct)

Or 2a=b is required for the 0's to be "the same"
But a=b, so no cigar.


       RM

--
http://www.piclist.com#nomail Going offline? Don't AutoReply us!
email .....listservKILLspamspam.....mitvma.mit.edu with SET PICList DIGEST in the body

2004\06\13@160822 by Wouter van Ooijen

face picon face
> > > (a-b)(a+b) = b(a - b)
> >
> > If a == b the (a-b) terms in the above line are a mathematical black
> > hole.
> >
> > Wouter van Ooijen
>
> No, they are perfectly well-defined and obey all the laws
> of mathematics.

Including the law that removing a factor of 0 at both sides of an
equation is not done?

Wouter van Ooijen

-- -------------------------------------------
Van Ooijen Technische Informatica: http://www.voti.nl
consultancy, development, PICmicro products

--
http://www.piclist.com#nomail Going offline? Don't AutoReply us!
email EraseMElistservspam_OUTspamTakeThisOuTmitvma.mit.edu with SET PICList DIGEST in the body

2004\06\13@162051 by William Chops Westfield

face picon face
On Sunday, Jun 13, 2004, at 06:49 US/Pacific, Jinx wrote:

These are usually pretty similar...
> I was sent
>
> If a = b, then:
> a^2 = a*b
> a^2 - b^2 = (a*b) - b^2
> (a-b)(a+b) = b(a - b)
>
If a=b, then a-b = 0, and you can't divide by 0.

> (a+b) = b
>
> Substitute the original a = b into the equation:
> 2b = b
> 2 = 1
>
BillW

--
http://www.piclist.com#nomail Going offline? Don't AutoReply us!
email listservspamspam_OUTmitvma.mit.edu with SET PICList DIGEST in the body

2004\06\13@180001 by Jinx

face picon face
> Took a few moments of staring :-)

Obvously it's an attention-getter. If it really worked it would
be part of tax legislation ;-(

--
http://www.piclist.com#nomail Going offline? Don't AutoReply us!
email @spam@listservKILLspamspammitvma.mit.edu with SET PICList DIGEST in the body

2004\06\15@091254 by Jinx

face picon face
> If a = b, then:
> a^2 = a*b
> a^2 - b^2 = (a*b) - b^2
> (a-b)(a+b) = b(a - b)
> (a+b) = b
> Substitute the original a = b into the equation:
> 2b = b
> 2 = 1

http://members.cox.net/mathmistakes/

--
http://www.piclist.com hint: PICList Posts must start with ONE topic:
[PIC]:,[SX]:,[AVR]: ->uP ONLY! [EE]:,[OT]: ->Other [BUY]:,[AD]: ->Ads

More... (looser matching)
- Last day of these posts
- In 2004 , 2005 only
- Today
- New search...